Is poor health literacy a risk factor for dementia in older adults? Systematic literature review of prospective cohort studies. (June 2019) - Oliveira, Deborah; Bosco, Alessandro; di Lorito, Claudio
Highlights: A bidirectional relationship exists between health literacy and cognitive function. This systematic review explored the relationship between health literacy and incident dementia in prospective cohort studies. Adjusted models showed that low health literacy leads to a higher dementia risk in older adults. Further research is required to establish the role of health literacy as a key risk factor for dementia. Abstract: Increasing evidence suggests a bidirectional relationship exists between levels of health literacy (HL) and cognitive impairment in later life. However, it is unclear whether low levels of HL can lead to a higher risk of dementia. This systematic review explored prospective cohort studies to find out whether HL is a risk factor for incident dementia in older adults. A search was conducted in Medline, PsycINFO, Embase, PubMed and Scopus and 5450 documents were initially retrieved. The grey literature and references of the selected papers were also consulted. Papers were selected and assessed by three researchers independently. Findings were reported in line with the PRISMA guidelines and quality appraisal was conducted using the STROBE checklist. Four studies were included for quality appraisal, data extraction and synthesis, all of which were conducted in the United States between 2014 and 2018. Adjusted analyses showed that in all studies people with low levels of HL had a significantly higher risk of incident dementia over time than people with adequate levels of HL. Low HL or total literacy (financial plus HL) was also a risk factor for mild cognitive impairment in two studies, irrespective of an Alzheimer's disease genotype. There was a statistically significant positive association between total literacy scores and the post-mortem amount of plaques and tangles suggestive of Alzheimer's disease. Our findings suggest that low levels of HL might lead to higher future dementia risk. However, as only a few longitudinal studies have been conducted in this area, further research is needed to establish the role of HL as a key risk factor for dementia. Researchers should use standardized HL-specific measurement tools so that future studies in this area are robust and comparable. Primary health care professionals might wish consider individual's HL when planning and implementing dementia risk reduction in order to improve its long-term effectiveness.